Komentar Positif Netizen Terhadap Film “Mencuri Raden Saleh” (Studi Netnografi Akun Instagram @mencuriradensalehfilm) - ramadhan, ervin restu (Widya Komunika, 2025)
Through a netnographic focus on the film's original Instagram account, @mencuriradensalehfilm, this analysis seeks to understand the positive comments made by netizens towards the film "Mencuri Raden Saleh". Famous actors such as Haque as Sarah the animal, Iqbaal Ramadhan as Piko the forger, and Angga Yunanda as Ucup the programmer appear in the film. "Mencuri Raden Saleh" is the story of a group of young people consisting of Ucup, a reliable programmer; Piko, a master forger; and Sarah, known as the "beast" because of her true abilities. They have a brilliant heist scheme where each of their collaborators must possess exceptional skills. Along the way, challenges arise that test their abilities, kinship, and inner characteristics. The audience is taken on an engaging and relatable journey through a gripping and riveting plot, which also powerfully and poignantly conveys important moral lessons about family, authenticity, and the consequences of their actions. This analysis identified and categorized positive comments from Instagram users who rated the movie "Stealing Raden Saleh" from various perspectives, including acting, plot, cinematography, and moral lessons. This was done using subjective methodology with netnography techniques. For one month after the movie was released, data was collected from Instagram comments related to the movie. The findings of the examination revealed that most of the compliments highlighted the acting skills of the cast, especially in reference to Iqbaal Ramadhan and Angga Yunanda's outstanding and unexpected performances. Netizens also gave high marks to the movie's script for its creativity and surprise factor, as well as its outstanding cinematography. Many people praised the movie for its ethical message, stating that it offers a very important motivation and example for family and sincerity.